Pengaruh Kualitas Lingkungan Keluarga, Association of Peers Group, Hidden Curriculum, dan Internet Social Media Exposure Terhadap Karakter Siswa (Studi pada SMK Negeri 2 Temanggung) - Azizah, Aullya Nurul; Bowo Santoso, Jarot Tri (Business and Accounting Education Journal, 2021)
The purpose of this research is to test the influence of family environment quality, association of peers group, hidden curriculum, and internet social media exposure to students’ character simultaneously or partially. The population of this study is all ten and twelve grade accounting students of Vocational High School 2 in Temanggung in the Academic Year of 2017/2018 in the number of 150 students. The sample used is 110 students that is taken using Slovin formula with proportionate random sampling technique. This study uses a quantitative approach with data collection methods using questionnaires. The method for analysing data used is descriptive statistic analysis and multiple regression analysis. The results of study indicated that family environment quality, association of peers group, hidden curriculum, and internet social media exposure simultaneously influenced on the students’ character 60.2%. While the partial variable family environment quality has a positive and significant effect by 27% to the students’ character, association of peers group has positive and significant effect by 26% to the students’ character, hidden curriculum has a positive and significant effect by 7% to the students’ character, while internet social media exposure has positive and significant affect by 4% to the students’ character.